Statistical modeling of lightweight concrete mixtures - Abdullahi M.; Al-Mattarneh H.M.A.; Mohammed B.S. (EuroJournals, Inc., 2023)
This paper employed a statistical technique for modeling of lightweight concrete mixtures using palm oil clinker (POC) as aggregate. POC is obtained from by-product of palm oil milling. The material is still new and accurate determination of its properties is very difficult. This makes the mix design of POC concrete a difficult task. Aggregate characterisation was conducted to determine the properties of palm oil clinker required for mix design. A central composite design (CCD) was used for the factor settings and mix design was conducted using absolute volume method. An experimental work was conducted involving 20 trial mixes at different factor and level combinations. Statistical modeling was done at 95% confidence interval. Test result shows that a polynomial model is adequate to predict the slump, air-dry density and compressive strength of POC concrete. The terms considered in the models were significant with p-values less than 0.05. The analysis of variance (ANOVA) shows that the developed models adequately fit the experimental data with a p-value for the regression less than 0.05. These statistics assures reasonable response prediction. Statistical approach has proved to be a useful tool for modeling of lightweight concrete mixture. EuroJournals Publishing, Inc. 2009.